The impact of commercial advertising on the public: (An Empirical Study) (Raparin Journal of Humanities (RJH), 2024)
Throughout the world, commercial advertising’s have become an art and effective method of communication. It is a recent necessity for all countries, nations, classes, and races. All of them are working on commercial advertising and commercial advertising are the work of all. It is crucial that the Commercial advertisements are used properly and must at a high level, Kurdish satellite channels can live and manage business in this way. Advertisements can provide facilities for citizens and consumers especially when The commercial advertisings were used properly and correctly of the direction and goals of the right and bright way. In Kurdistan Region, commercial advertisements have passed through a short period of time. In the early stages they were at a very low level, until they were within technology development and the emergence of necessary instructions to organize advertising ,becoming more advanced and developed.The significance of this research which is a scientific attempt to demonstrate and determine the effect of the commercial advertisements of The Kurdish Channels in encouraging behavior of transaction by a pattern of This research ambition is to certify the emphasis extent of advertising Commercial advertisements on Kurdish channels. To what extent Kurdish satellite channels encourage consumer’s behavior to acquisitions Goods? Which are the business rhetoric that attracts more consumer attention to buy equipments. This research is a described research, we have used the method of surveying that is the most appropriate The method is set because the most accurate data and information can be obtained in this way. This research in which the theory of relying on practical media tools.It is one of the most significant theories in the domain of media. The society of this research consists of the population of Kurdistan region which consists of 500 individuals of male and female in all four provinces of Region (Erbil ,Sulaymaniyah ,Duhok and Halabja) participated in it. the researcher to collect data and Knowledge and achievement of research studies survey formused it, and in this study, the statistical text known as the SPSS system It's used.The most important results of the research are: the relationship between commercial advertising and Kurdish channels which Are a strong and effective direct connection, and a connection between commercial advertising and buying, it is a strong and effective direct relationship, in addition to commercial advertisements on Kurdish-sourced satellite channels.the importance of user information in selecting the necessary goods and services for the election It's the best choice. In addition, commercial advertising on Kurdish airlines has an important role to play in building trust and agreement with the Kurdistan Regional Government, particularly on topics that have been advertised commercially.